Analysis of Creating Shared Value in the Food and Beverage Industry - Saraswati, Erwin (Jurnal Ilmiah Akuntansi dan Bisnis; Vol 16 No 1 (2021), 2021)
This study analyzed the creating shared value (CSV) concept in the food and beverage industry using descriptive quantitative method. CSV is the practice of creating corporate policies and practices that enhance a company's competitiveness while simultaneously advancing the social and economic conditions in communities in which the company sells and operates. It is considered an enhanced version of CSR, which emphasizes the synchronization between social and economic progress. Thirteen listed food and beverage companies in Indonesia from 2015 to 2017 were analyzed, resulting in 39 firm-year observations. We conducted a content analysis on the sample CSR reports using Drozdz et al.’s (2015) indicators. Our analysis showed that companies created value mostly for their customers, since customers are especially important for these firms because of their prominent nature. The result supports the legitimacy theory, which stated that companies need to align their operations with the expectations of the society they operate in order to survive. In addition, the result suggests that food and beverage companies need to start creating more shared values for the society, their employees, the environment, and their suppliers. The CSV concept can be a strategic practice for companies.